Analiza kakovostne strukture okroglega lesa listavcev - Krajnc, Luka (Les (Ljubljana), 2023)
The research presented in this study addressed the distribution of volume across different log grades in three hardwood species: European beech (Fagus sylvatica L.), sycamore maple (Acer pseudoplatanus L.) and English oak (Quercus robur L.). Standing trees were selected, marked, and measured. Afterwards the trees were felled and bucked into assortments according to national legislation regarding assortment grades and requirements for each assortment grade. Each individual assortment was measured and classified into one of the national log quality grades. Proportions of log volume with different grades within individual tree volumes were calculated and presented in this study. Differences were found in log grade volume distribution between different species and diameter classes. By following the national grading system for assortments, between 40% and 50% of total volume will be usable assortments in hardwoods
Keywords: hardwoods; hlodovina; kakovost; listavci; log grading; logs; prostornina; quality; sortimentacija; volume